CXCL1 microspheres: a novel tool to stimulate arteriogenesis. (12th October 2016) - Caolo, Vincenza; Vries, Mark; Zupancich, John; Houben, Marcel; Mihov, George; Wagenaar, Allard; Swennen, Geertje; Nossent, Yaël; Quax, Paul; Suylen, Dennis; Dijkgraaf, Ingrid; Molin, Daniel; et al.
Abstract: Context : After arterial occlusion, diametrical growth of pre-existing natural bypasses around the obstruction, i.e. arteriogenesis, is the body's main coping mechanism. We have shown before that continuous infusion of chemokine (C-X-C motif) ligand 1 (CXCL1) promotes arteriogenesis in a rodent hind limb ischemia model. Objective : For clinical translation of these positive results, we developed a new administration strategy of local and sustained delivery. Here, we investigate the therapeutic potential of CXCL1 in a drug delivery system based on microspheres. Materials and methods : We generated poly(ester amide) (PEA) microspheres loaded with CXCL1 and evaluated them in vitro for cellular toxicity and chemokine release characteristics. In vivo, murine femoral arteries were ligated and CXCL1 was administered either intra-arterially via osmopump or intramuscularly encapsulated in biodegradable microspheres. Perfusion recovery was measured with Laser-Doppler. Results : The developed microspheres were not cytotoxic and displayed a sustained chemokine release up to 28 d in vitro . The amount of released CXCL1 was 100-fold higher than levels in native ligated hind limb. Also, the CXCL1-loaded microspheres significantly enhanced perfusion recovery at day 7 after ligation compared with both saline and non-loaded conditions (55.4 ± 5.0% CXCL1-loaded microspheres versus 43.1 ± 4.5% non-loaded microspheres; n = 8–9; p < 0.05). On day 21 after ligation, the CXCL1-loaded microspheres performed even better than continuous CXCL1 administration (102.1 ± 4.4% CXCL1-loaded microspheres versus 85.7 ± 4.8% CXCL1 osmopump; n = 9; p < 0.05). Conclusion : Our results demonstrate a proof of concept that sustained, local delivery of CXCL1 encapsulated in PEA microspheres provides a new tool to stimulate arteriogenesis in vivo .